Kebebasan Wanita dalam Menentukan Calon Suami: Perspektif Hukum Positif dan Fiqh - Adityo, Rayno Dwi (Morality: Jurnal Ilmu Hukum; Vol 6 No 2 (2020): Morality :Jurnal Ilmu HukumDO - 10.52947/morality.v6i2.172, 2020)
Forced mariages is social phenomena, because often occurs, majority who are often victim is women and it often happen inside or outside the family. Forced marriages seeming to be an tradition, the patterns is varied. Someone is forced to marriage, because their paradigm is the solution of resolve the problem inside their family. Specific purpose is to give a holistical description that the women have a right to choosed their own husband without compulsion. The Metodology used legal normative and kualitatif approach. The result is, first, even though, the forced marriages is contradictory with the positiv law dan so the fiqh perspective, and the second, from social approach that forced mariages is have relation with culture, education, and a narrow interpretation of text religion sources. The truth is that a women right to choosed a man who will be her husband.